Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a)
\(4\left(x-1\right)-\left(3x+2\right)=16\)
=> 4x - 4 - 3x - 2 = 16
=> x - 6 = 16
=> x = 22
Vậy .......
b)
\(7\left(x-5\right)+5\left(15-x\right)=130\)
=> 7x - 35 + 75 - 5x = 130
=> 2x + 40 = 130
=> 2x = 90
=> x = 45
Vậy........
c)
\(30\left(x-2\right)-6\left(x-5\right)-22x=100\)
=> 30x - 60 - 6x + 30 - 22x = 100
=> 2x - 30 = 100
=> 2x = 130
=> x = 65
Vậy.....
d) \(x-17+x=x-23\)
=> 2x - 17 = x - 23
=> x = -6
Vậy .......
=>100.18:[(5x+130):x]=100
=>1800:[(5x+130):x]=100
=>(5x+130):x=1800:100=18
=>5x:x+130:x=18
=>\(\frac{5x}{x}+\frac{130}{x}=18=>\frac{5x+130}{x}=18=>5x+130=18x=>18x-5x=130\)
=>13x=130=>x=10
a) 25 - 3x = 13
3x = 25 - 13
3x = 12
x = 12 : 3
x = 4
b) 13 + 3(130 - 3x) = 313
3(130 - 3x) = 313 - 13
3(130 - 3x) = 300
130 - 3x = 300 : 3
130 - 3x = 100
3x = 130 - 100
3x = 30
x = 30 : 3
x = 10
1)
a)2x+26-84+7x=-130
(2x+7x)+(-84+26)=-130
9x-58=-130
9x=-130+58
9x=-72
x=-72/9
x=-8
Vậy x=-8
b)-6x+12+12-8x=-130
(-6x-8x)+(12+12)=-130
-14x+24=-130
-14x=-130-24
-14x=-154
x=-154/(-14)
x=11
Vậy x=11
c)4x-26-8=3x-69
4x-3x=-69+26+8
x=-35
Vậy x=-35
\(100-3x=-130\)
\(3x=100-\left(-130\right)\)
\(3x=230\)
\(x=230:3\)
\(x=\dfrac{230}{3}\)
Vậy .....
\(100-3x=-130\)
\(\Rightarrow3x=230\Rightarrow x=\dfrac{230}{3}\)
Vậy.........
Chúc bạn học tốt!!!